Evaluation of anti-inflammatory and wound healing properties of Tinospora cordifolia extract - Shohag Chandra Das; Subrato Biswas; Olin Khan; Rupa Akter; Md Abul Kalam Azad; Sujan Kumar Sarkar; Md. Abdul Masum; Sultana Bedoura (PLoS ONE, 2025)
Tinospora cordifolia extract exhibits diverse benefits—anti-arthritis, anti-malarial, anti-allergic, anti-diabetic, antihepatotoxic, and antipyretic effects. Its specific anti-inflammatory and healing capacities remain unexplored, prompting a study utilizing a mouse skin wound model and direct T. cordifolia extraction. UV-Vis spectroscopy depicted an absorption range of 200–400 nm, while FTIR analysis identified alcohols, phenols, amines, amides, aldehydes, ketones, alkanes, and alkenes. GC-MS analysis revealed the presence of components: 5methyl-5-Hexen-2-Ol, n-hexadecenoic acid, cholesta-4,6-dien-3beta-ol, stigmasterol, β-sitosterol, stearate which are present in the extract. Histopathological examination confirmed accelerated wound healing, showcasing reduced inflammation, restored blood vessels, collagen fibers, and swift epidermal closure. T. cordifolia extract exhibits promise in enhancing wound healing through its antibacterial, anti-inflammatory properties.